Qualitative Analysis of Multiple Choice Test Instruments in Grade V PAI Subjects at SDN Rowokangkung 01 - Waliyyuddin, Rifqi 'Athif; Yusuf, Mochamad; Zuhriah, Indah Aminatuz (Yayasan Rahmat Islamiyah, 2024)
The purpose of this study was to determine the quality of multiple-choice items on the end-of-semester summative questions on PAI subjects at SDN Rowokangkung 01 Lumajang, the analysis was carried out qualitatively in terms of material aspects, construction aspects and language aspects. This type of research is qualitative research with descriptive-analytical method, while the research data is obtained through documentation method. From this study it can be concluded that in terms of the three aspects, the questions have met the criteria of good and feasible use.